Flecainide toxicity in renal failure. Issue 3 (3rd July 2018) - Subedi, Rogin; Dean, Ryan K.; Chaudhary, Arbind; Szombathy, Tamas
ABSTRACT: Flecainide, a class Ic antiarrhythmic, is used for the prevention of paroxysmal supraventricular tachycardia, paroxysmal atrial fibrillation/flutter, and sustained ventricular tachycardia. Flecainide is primarily metabolized by the liver and to a lesser extent (30%) is excreted unchanged in the kidney. We present a case of flecainide toxicity in the setting of renal impairment that was successfully treated with intravenous sodium bicarbonate.